Development of an implementation science informed “Test Evidence Transition” program to improve cancer outcomes - Hamilton-West, Kate E.; Feast, Alexandra; Masento, Natalie A.; Knowles, Brian; Sloan, Claire; Weaver, Luke (Frontiers in Health Services, 2024)
Introduction: Translation of cancer research into practice takes around 15 years. Programs informed by implementation science methods and frameworks offer potential to improve cancer outcomes by addressing the implementation gap.Methods: We describe the development of a Test Evidence Transition (TET) program which provides funding and support to health system delivery teams and project design and evaluation partners working together to achieve three objectives: Test innovations to support optimal cancer pathways that transform clinical practice; Evidence the process, outcome, and impact of implementation; and work with strategic partners to ensure the Transition of best practice into effective and equitable adoption across UK health systems.Results: Phase 1 launched in April 2023. Teams with the capability and motivation to implement evidence-based pathway innovations were identified and invited to submit expressions of interest. Following peer-review, teams were supported to develop full proposals with input from academics specializing in health services research, evaluation, and implementation science. Projects were selected for funding, providing an opportunity to implement and evaluate innovations with support from academic and health system partners.Conclusions: TET aims to improve cancer outcomes by identifying and addressing local-level barriers to evidence-based practice and translating findings into consistent and equitable adoption across health systems. Phase 1 projects focus on pathway innovations in diagnosis for breast and prostate cancer. We are now launching Phase 2, focusing on colorectal cancer.